A Sustainable Marketing Strategy Based on Customer Satisfaction: The Case of Dongbu Insurance in South Korea - Kang, Sunhee; Kang, Bohyeon (Indian Journal of Marketing, 2014)
In Market 3.0, where customers are participating in corporate business actions and decision making, the customers' role has become more important and has even turned into a core value every company should observe carefully in order to maintain it longer. Consequently, the only way to be more competitive is by adopting customer-centered key values. Dongbu Insurance, one of the top three insurance companies in South Korea, became a successful company by adopting this customer-centered management and has further developed its marketing strategy accordingly. The main purpose of this case study was to examine how the Korean insurance company overcame internal and external critical situations utilizing a competitive marketing mix strategy and how it became one of the most successful and sustainable insurance companies in Korea. To investigate this, secondary data analysis and comparative research methods were used according to the chronological improvements made by the insurance firm. This study stressed that the key factors of Dongbu's marketing mix strategy focused on customer satisfaction. Two crucial lessons that this study revealed about Dongbu Insurance is the importance of developing real customer-centered products and raising brand awareness and recognition by utilizing various channels such as call centers, SNS, blogs, customer evaluation groups, and the Promy brand. This case study would help the insurance industry to comprehend the importance of adopting a customer-centered marketing mix strategy in a hostile business environment. However, the findings from this research may not be generalized due to the fact that only one company case - Dongbu Insurance - was chosen from South Korea.